(NtEOR)QÆQ UKRAÇNSXKOGO NARODNOGO TANC@ (B/s)E - (NwERHOWINECX(B, (NwASILX mIKOLAJOWI^(B,s ((NkI)QÇW (B:s)E (NmISTECTWO(B,s, 1968)
(NtEOR)QÆQ UKRAÇNSXKOGO NARODNOGO TANC@(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NmISTECTWOs -- (NhOREOGRAF)QÆQs)E -- (NnARODNIJ TANECXs; (NUKRA)QÇNSXKÆ NARODNÆ TANCÆs)E; (NGOPAKs; (NKOZA^OKs; (NMAR[s